Development of Mobile Learning integrated with Learning Management System (LMS) on Buffer Solutions Topic - Ucu Cahyana; Farihatul Janah; Setia Budi (Jurnal Tadris Kimiya, 2021)
This research aims to develop mobile learning integrated with LMS and test its effectiveness motivation learning on the topic of buffer solutions. The research was conducted at SMA AL-HASRA from November 2020 to June 2021. The research and development method by Borg and Gall was used by modifying five stages, needs analysis; product development; validation; product testing; and implementation. Testing used quantitative method with post-test only control group design and analysis using independent sample t-test. The resulting mobile learning medium is called "LarutanPenyangga.apk" which is compatible with Android devices which provides summaries, video animations, kimi, quiz, and application buffer solutions in daily life. The feasibility test for topic and language resulted 82.25% with a reliability 0.975. The feasibility test for media 75.05% with a reliability 0.960. Trial test have very good criteria. The effectiveness test of motivation learning percentage is 68.4% and has a good category. Based on the t-test, obtained ttable < tcount. It can be concluded that H0 is rejected and H1 is accepted, which means that there is a significant positive effect from the use of integrated mobile learning with LMS to increase students' learning motivation on buffer solutions topic.